2016
DOI: 10.4014/jmb.1510.10102
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Barcode-Based Analysis of Exoelectrogens in Wastewater Biofilms Grown on Anode Surfaces

Abstract: The most energy-demanding step of wastewater treatment is the aeration-dependent elimination of organic carbon. Microbial fuel cells (MFCs) offer an alternative strategy in which carbon elimination is conducted by anaerobic microorganisms that transport respiratory electrons originating from carbon oxidation to an anode. Hence, chemical energy is directly transformed into electrical energy. In this study, the use and stability of barcodecontaining exoelectrogenic model biofilms under non-axenic wastewater trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The preincubation was supposed to steer the oxidation process in the reactors towards anode reduction and to accelerate the anode reduction process. In previous experiments, it could be shown that, under certain process conditions, the preincubation can lead to stable biofilms that remain on the anode even under non-axenic conditions [ 25 ]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preincubation was supposed to steer the oxidation process in the reactors towards anode reduction and to accelerate the anode reduction process. In previous experiments, it could be shown that, under certain process conditions, the preincubation can lead to stable biofilms that remain on the anode even under non-axenic conditions [ 25 ]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate of the system was changed under strictly anoxic conditions in an anoxic glove box. Coulombic efficiencies of the chronoamperometric experiments were calculated as described previously [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All strains used in this study are listed in Table 1. S. oneidensis barcode is a strain that was developed by Dolch et al (2016). It contains a 72 bp synthetic genomic integration that can be used for the quantification of cells via quantitative PCR (qPCR, see below).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA isolation as well qPCR based cell quantification were conducted according to Dolch et al (2016).…”
Section: Methodsmentioning
confidence: 99%